Association Between Factory Workers’ Profile with Chest X-ray Finding and Spirometry at Industrial Company of X - Wijaya, Dewi; Esha, Indi; Adrianison, Adrianison; Simatupang, Elvando Tunggul Mauliate; Amarudin, Amarudin (Indonesian Society of Respirology (ISR), 2025)
Background: Factory workers are a group at high risk of developing occupational lung abnormalities. Continuous exposure to dust, smoke, or gas particles during work processes may lead to progressive lung damage. Chest X-ray and spirometry are essential diagnostic tools for assessing both structural and functional lung changes, allowing early detection and prevention of occupational lung disability, especially among workers exposed to airborne pollutants. Method: This analytical observational study employed a cross-sectional design to analyze the association between factory workers’ profiles and chest X-ray and spirometry findings. Lung function was assessed using spirometry parameters, including Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV₁), and FEV₁/FVC ratio to identify restrictive or obstructive patterns. Data were collected using total sampling during periodic health examinations and analyzed with SPSS version 26.0. Descriptive statistics were used to summarize characteristics, while inferential analysis using Chi-square or Fisher’s exact tests was conducted to determine associations between categorical variables, with a significance level set at P<0.05. Results: A total of 260 factory workers participated, most with ≤5 years of work experience (60.76%). Comorbidities were significantly associated with both chest X-ray findings and lung function (P=0.034 and P=0.004). Smoking history and length of work also showed significant relationships with lung function (P=0.027 and P=0.019). Conclusion: There is a significant association between smoking history and length of work with changes in lung function. Meanwhile, comorbidities have a significant association with lung structure and lung function. Periodic evaluation using spirometry and chest X-ray is essential for early detection and prevention of occupational lung abnormalities among factory workers.